Impacts of Financial Literacy and Confidence on the Severity of Financial Hardship in Australia - Evgenia Bourova; Malcolm Anderson; Ian Ramsay; Paul Ali (Australasian Accounting, Business and Finance Journal, 2019)
Consumers in Australia and other developed countries are increasingly required to interact with providers of complex financial products and services, and to estimate, mitigate or absorb the risks that flow from their financial decisions. A range of debt-related problems in Australia have been attributed to low levels of financial literacy in the population. However, there has been limited research exploring the relationship between low financial literacy and the problem of financial hardship, where a consumer takes on payment obligations under a contract, but then becomes unable to meet them when they fall due. Drawing on a survey of Australians who recently experienced debt problems, this article examines the impact of financial literacy levels and levels of confidence in managing day-to-day spending on severity of financial hardship. The article also examines the impacts of financial literacy and confidence levels on the strategies employed to get by financially while in debt. The article shows that while there is no straightforward relationship between low financial literacy and severity of financial hardship, lower levels of financial literacy may reduce consumers’ ability to avoid some of the more serious consequences of default, particularly if coupled with overconfidence about their ability to manage spending.
Keywords: Financial literacy; financial hardship; overconfidence; Australia.